Imaging dopamine - Cumming, Paul (Cambridge University Press, 2009)
Since its discovery 50 years ago, brain dopamine has been implicated in the control of movement and cognition, and is concerned with diverse brain diseases such as Parkinson's disease, schizophrenia and drug addiction. This book is an illustrated biography of the dopamine molecule, from its synthesis in the brain to its signalling mechanisms and ultimately to its metabolic breakdown. Using colour illustrations of positron emission tomography (PET) scans, each chapter presents a specific stage in the biochemical pathway for dopamine. Writing for researchers and graduate students, Paul Cumming presents a compilation of all that has been learned about dopamine through molecular imaging, a technology which allows the measurement of formerly invisible processes in the living brain. He reviews current technical controversies in the interpretation of dopamine imaging, and presents key results illuminating brain dopamine in illness and health.